2016
DOI: 10.1111/jfpp.12866
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Combined Effect of Chitosan and Lactic Acid Bacteria inAlheira(Fermented Meat Sausage) Paste

Abstract: This study aimed to assess the efficacy of chitosan, Pediococcus acidilactici HA‐6111‐2 (bacteriocinogenic strain with antilisterial activity) and Pediococcus pentosaceus HA‐3083‐3 (a nonbacteriocinogenic strain), added individually or in combination, in the control of Listeria innocua, Staphylococcus aureus, Escherichia coli and Salmonella typhimurium during storage of Alheira paste at 4C. The behavior of pathogenic bacteria in the food matrix was significantly affected by the addition of chitosan. Chitosan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…In the study of Casquete et al [ 24 ], the authors used the agar dilution method and obtained the MIC values of chitosan 0.02%, 0.2%, 0.02%, and 0.1% ( w/v ) for Staphylococcus aureus, Listeria innocua, Escherichia coli, and Salmonella Typhimurium, respectively. However, in this study, only the MIC value obtained for S. Typhimurium ESB9 was similar (0.15% w/v , at pH 7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Casquete et al [ 24 ], the authors used the agar dilution method and obtained the MIC values of chitosan 0.02%, 0.2%, 0.02%, and 0.1% ( w/v ) for Staphylococcus aureus, Listeria innocua, Escherichia coli, and Salmonella Typhimurium, respectively. However, in this study, only the MIC value obtained for S. Typhimurium ESB9 was similar (0.15% w/v , at pH 7).…”
Section: Resultsmentioning
confidence: 99%
“…However, differences in antimicrobial activities may be due to several factors, including the type of chitosan, the degree of deacetylation, the molecular weight, and the bacterial strains. In addition, the pH value, strength, and presence of ionic solutes in the culture media may be capable of reacting with chitosan through molecular interactions and blocking the reactivity of the amine group and also the presence of substances that might interfere [ 24 , 32 ]. In this study, different pH values also influenced inhibition by chitosan, as well as the in vitro method used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this chitosan effect on lactic acid concentration occurred only in silos without microbial inoculant. Casquete, Castro, and Teixeira (), found an associative effect between chitosan and LAB ( Pediococcus spp.) on food conservation, in which chitosan inhibits LAB growth after 7 days of incubation.…”
Section: Discussionmentioning
confidence: 98%
“…Although those authors reported that CHI had a positive impact on lactate content, DM recovery, and in vitro degradation of WPSS, there was no associative effect. Casquete et al (2016) observed that chitosan utilization in food conservation inhibits aerobic and pathogenic bacteria growth. They also reported a synergistic effect with LAB inoculation, which potentially inhibits the growth of deteriorating microorganisms during the aerobic stage of ensiling and improves silage fermentation.…”
Section: Introductionmentioning
confidence: 99%